Pelvic floor behavioral treatment for fecal incontinence and constipation in quiescent inflammatory bowel disease. (3rd July 2022) - Khera, Angela J.; Chase, Janet W.; Stillman, Barry C.; Salzberg, Michael; Thompson, Alexander J. V.; Basnayake, Chamara; Wilson-O'Brien, Amy; Kamm, Michael A.
Abstract: Background and aim: Refractory bowel symptoms in quiescent inflammatory bowel disease (IBD) are common but evidence for effective management is limited. We aimed to determine whether behavioral treatment, including pelvic floor muscle training, decreases the severity of functional bowel symptoms in patients with quiescent IBD. Secondary aims were to evaluate the treatment effect on quality of life, psychological well-being and pelvic floor muscle function. Methods: This prospective study included IBD patients in remission with persistent symptoms of fecal incontinence or constipation who received up to six sessions of behavioral treatment at monthly intervals. The primary outcome was patient-rated symptom improvement on a 7-point Likert scale (1 = substantially worse, 7 = substantially better). Secondary outcomes included validated symptom scores, quality-of-life, psychological measures, and transperineal ultrasound assessment of pelvic floor muscle activity. Results: Thirty-four patients (median age 38 years; 24 females; 18 ulcerative colitis, 13 Crohn's disease, 3 ileo-anal pouch) were included. Twenty-one of the 29 (72%) patients who completed treatment, or 21 of all 34 (62%) patients, reported moderate or substantial improvement (patient rating of 6 or 7). Symptom scores ( p  < .001), IBD-specific quality of life ( p  = .008) and illness perception scores ( p  = .003) significantly improved. General quality of life, and anxiety and depression scores, did not change significantly. Transperineal ultrasound pelvic floor measures did not correlate with patient-rating of symptom improvement. Conclusion: Significant symptomatic improvement occurred in a majority of patients with quiescent IBD. Behavioral treatment should be considered for patients with quiescent IBD and ongoing functional bowel symptoms of fecal incontinence, fecal urgency, or constipation.